The Influence of Work Motivation, Competency and Work Environment on Employee Performance at PT. Bukit Palem Singkup District, Ketapang District, West Kalimantan Province - Putri, Yolidya Agita; Prayekti, Prayekti; ,, Epsilandrisptyarini (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This research aims to analyze the influence of work motivation, competence and work environment on employee performance at PT. Bukit Palem, Singkup District, Ketapang Regency, West Kalimantan Province. In the research carried out using a quantitative approach with a survey method and the population used was 320 permanent employees and the sample size was purposive sampling and regression data techniques which the researchers took were 76 working respondents. The results of the analysis show that work motivation and competence have a positive and significant effect on employee performance, besides that the work environment and work motivation also have a positive and significant effect on employee performance. The research was conducted using a quantitative approach with survey methods. Quantitative methods are used in this research because the data obtained in this research is in the form of numbers which have scores from the hypothesis results for the data. The survey method is a method where samples are taken from a population and using a questionnaire as the main data collection tool. In survey research, information is obtained from respondents using a questionnaire (Sugiyono, 2019). In this research, the population used is permanent employees who work in PT. Bukit Palem, Singkup District, Ketapang Regency, West Kalimantan Province, numbering 320 employees. The number of samples taken by researchers were permanent employees who worked, namely 76 respondents. Sample technique, regression data analysis using questionnaire data.